2012
DOI: 10.1159/000337752
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Granular Proteins Damage Bronchial Epithelial Cells Infected with Respiratory Syncytial Virus

Abstract: Background: Respiratory syncytial (RS) virus infection is an important exacerbating factor in acute bronchial asthma. However, the precise mechanisms responsible for viral infection-induced exacerbations of asthma are uncertain. To elucidate the role of eosinophilic inflammation in the pathogenesis of virus-induced asthma, we investigated the effects of eosinophil granule proteins on bronchial epithelial cell infected with RS virus. Methods: Morphological changes and cytopathic effects in human type II pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…The eosinophil granule proteins, major basic protein (MBP), eosinophil cationic protein (ECP), eosinophil derived neurotoxin (EDN) and eosinophil peroxidase (EPO), are eosinophil effector molecules implicated in host defense (Malik and Batra, 2012), immunoregulatory responses (Yang et al, 2008) and allergic and inflammatory reactions (Sedgwick et al, 2004; Kato et al, 2012; Lee et al, 2013). These highly cationic proteins are stored preformed within the secondary granules of eosinophils, and can be released in intact membrane-bound granules during cell lysis or through a complex system of vesiculotubular structures during “piecemeal necrosis” (reviewed in (Muniz et al, 2012)).…”
Section: Introductionmentioning
confidence: 99%
“…The eosinophil granule proteins, major basic protein (MBP), eosinophil cationic protein (ECP), eosinophil derived neurotoxin (EDN) and eosinophil peroxidase (EPO), are eosinophil effector molecules implicated in host defense (Malik and Batra, 2012), immunoregulatory responses (Yang et al, 2008) and allergic and inflammatory reactions (Sedgwick et al, 2004; Kato et al, 2012; Lee et al, 2013). These highly cationic proteins are stored preformed within the secondary granules of eosinophils, and can be released in intact membrane-bound granules during cell lysis or through a complex system of vesiculotubular structures during “piecemeal necrosis” (reviewed in (Muniz et al, 2012)).…”
Section: Introductionmentioning
confidence: 99%
“…Further study is needed to clarify the implications. Meanwhile, other authors reported a positive relationship between eosinophil infiltration and STAT3 in nasal polyp [29] or bronchial epithelial damage by virus infection [30].…”
Section: Discussionmentioning
confidence: 99%
“…The viral titer of the pooled purified RSV was 2.0 × 10 8 TCID 50 (50% of tissue culture infectious dose)/0.1 ml. Full inactivation of RSV was achieved by exposing a sterile glass vial containing viral suspension to an ultra violet (UV) light source (302 nm) for 16 h at 4°C as previously reported [12,13]. …”
Section: Methodsmentioning
confidence: 99%